Genetic Diversity in Brassica rapa L. - Khatun, H; Rasul, MG; Saikat, MMH; Haque, MM (Bangladesh Journal of Plant Breeding and Genetics, 2011)
The genetic diversity was assessed in 42 Brassica rapa genotypes for identifying parental genotypes having distant relationship for hybridization. All the genotypes were analyzed through principal component analysis, principal coordinate analysis canonical variate analysis and non-hierarchical clustering which compute Mahalanobis’s D2 statistics. The genotypes under study were grouped into six clusters. The cluster V contained the maximum numbers of genotypes (15) and cluster III had the minimum number of genotypes (3). The highest intra-cluster distance was observed in cluster V that represented maximum variability within the cluster and Cluster VI had the lowest intra-cluster distance. The maximum inter cluster distance was noticed between the clusters II and III and the lowest between clusters II and VI. Cluster with large distances were considered more diverged than those with small distances. Yield and yield contributing characters such as days to 1st flowering, number of siliquae on main racemes, number of siliquae per plant, number of seeds per siliqua, 1000 seeds weight and seed yield per plant contributed more towards genetic divergence considering diversity pattern. Considering cluster distance, inter-genotypic distance, cluster mean and other agronomic performances genotypes BC-200502, BC-200505, BC-200506, BC-200510, BC-200512, BC-200515, BC-200519, BC-200521, BC-200529, BC-200530, BC-200531B, BC-200531Y, BC-200536, BC-200537, BC-200542, BC-200543, BARI Sarisha 12, and BARI Sarisha 14 may be selected from different clusters for hybridization program. Key words: Genetic divergence; Brassica rapa; cluster analysis; D2-statistics DOI: http://dx.doi.org/10.3329/bjpbg.v23i1.9315 BJPBG 2010; 23(1): 31-37